2001
DOI: 10.1121/1.1323236
|View full text |Cite
|
Sign up to set email alerts
|

The radiation efficiency grouping of free-space acoustic radiation modes

Abstract: The use of a modal representation for the exterior acoustic field of a structure has received increasing attention in recent years. This modal approach generally seeks a set of orthogonal functions, representing independent surface velocity distributions, termed acoustic radiation modes, which diagonalize a radiation operator in the exterior domain of the structure. These orthogonal acoustic radiation modes may be found, among other methods, through an eigenvalue analysis of a radiation operator and possess a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 26 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…In Fig. 4, the grouping behavior of the exterior radiation mode eigenvalues can be observed as described by Cunefare et al 15 and by Wu et al 40 and as obtained for the circle in Sec. 5.1, which is a pure exterior acoustic problem without holes or chambers with interior modes.…”
Section: Influence Of Infinite Elements On Radiation Modesmentioning
confidence: 61%
See 2 more Smart Citations
“…In Fig. 4, the grouping behavior of the exterior radiation mode eigenvalues can be observed as described by Cunefare et al 15 and by Wu et al 40 and as obtained for the circle in Sec. 5.1, which is a pure exterior acoustic problem without holes or chambers with interior modes.…”
Section: Influence Of Infinite Elements On Radiation Modesmentioning
confidence: 61%
“…3. The grouping behavior of ARM eigenvalues or radiation efficiencies in terms of acoustical multipoles has already been presented by Cunefare et al 15 for three-dimensional problems and by Wu et al 40 …”
Section: Circlementioning
confidence: 98%
See 1 more Smart Citation
“…23 Therefore, unlike the spherical harmonics, the ARMs are frequency dependent, which might lead to impractical spatial filters as far as loudspeaker arrays for directivity control are concerned. However, simulation results have indicated that the ARMs of the PSLs do not depend on frequency, 13,26 although a mathematical proof has not been presented so far.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to basis elements that radiate sound energy independently and decay with distance at very different rates in the near field, such as the spherical harmonics and the ARMs. [22][23][24] Hence, the regularization technique generally adopted consists in discarding the eigenvectors (or eigenfunctions) associated to very small eigenvalues, which arise from strongly decaying waves, especially at low frequencies.…”
Section: Introductionmentioning
confidence: 99%